The Professional Education and Development of Teachers of Mathematics The 15th ICMI Study - Even, Ruhama; Ball, Deborah Loewenberg; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
The premise of the 15th ICMI Study is that teachers are key to students' opportunities to learn mathematics. What teachers of mathematics know, care about, and do is a product of their experiences and socialization, together with the impact of their professional education. The Professional Education and Development of Teachers of Mathematics assembles important new international work- development, research, theory and practice - concerning the professional education of teachers of mathematics. As it examines critical areas to reveal what is known and what significant questions and problems warrant collective attention, the volume also contributes to the strengthening of the international community of mathematics educators. Preparing and maintaining a high-quality, professional teaching force that can teach mathematics effectively and prepare youth for a future of social responsibility is a worldwide challenge. As such, systems of teacher education, both initial and continuing, are essential to the success of mathematics educators and their students. More international exchange of knowledge and information about the professional development would certainly benefit both groups, and this volume seeks to address the need. The Professional Education and Development of Teachers of Mathematics offers a cross-cultural conversation about mathematics teacher education in mathematics around the world with attention given to research, theory, practice and policy.
Initial Mathematics Teacher Education -- The Preparation of Teachers -- Overview of Teacher Education Systems Across the World -- Components of Mathematics Teacher Training -- Practising Mathematics Teacher Education: Expanding The Realm of Possibilities -- Learning to Teach Mathematics: Expanding the Role of Practicum as an Integrated Part of a Teacher Education Programme -- Student Teachers$1 (BExperiences and Early Years of Teaching -- Studying Student Teachers$1 (BVoices and Their Beliefs and Attitudes -- School Experience During Pre-Service Teacher Education from the Students$1 (BPerspective -- 1.2.3 -- Mathematics EducatorS$1 (BActivities and Knowledge -- Mathematics Educators$1 (BKnowledge and Development -- Becoming a Teacher Educator: Perspectives from the United Kingdom and the United States -- Educators Reflecting on (Researching) Their Own Practice -- Educators and the Teacher Training Context -- Initial Mathematics Teacher Education: Comments and Reflections -- Initial Mathematics Teacher Education: Comments and Reflections -- Learning in and from Practice -- Development of Teaching in and from Practice -- Mathematics Teachers$1 (BProfessional Development: Processes of Learning in and from Practice -- Tools and Settings Supporting Mathematics Teachers$1 (BLearning in and from Practice -- The Balance of Teacher Knowledge: Mathematics and Pedagogy -- Learning in and from Practice: Comments and Reflections -- Established Boundaries? A Personal Response to Learning in and from Practice -- Key Issues for Research in the Education and Professional Development of Teachers of Mathematics -- Some Reflections on Education, Mathematics, and Mathematics Education -- Toward a More Complete Understanding of Practice-Based Professional Development for Mathematics Teachers -- Public Writing in the Field of Mathematics Teacher Education -- Strengthening Practice in and Research on the Professional Education and Development of Teachers of Mathematics: Next Steps -- Setting the Stage for the ICMI Study on the Professional Education and Development of Teachers of Mathematics -- Setting the Stage for the ICMI Study on the Professional Education and Development of Teachers of Mathematics.s
Keywords: Education; Mathematics -- Study and teaching; Teaching; Education; Mathematics Education; Teaching and Teacher Education; Electronic books